Economic Development Of Rantau Karya Village Community Air Sugihan District, Ogan Komering Ilir Regency 2011 – 2017 (Contribution Of Materials To The Course Economic History Of History Education Of Sriwijaya University) - Mindarto Mindarto; Yunani Yunani; Alian Alian (Criksetra: Jurnal Pendidikan Sejarah, 2018)
This study entitled "Economic Development of the Community of Rantau Karya Village in Air Sugihan Subdistrict, Ogan Komering Ilir Regency in 2011-2017" with three problem formulations namely: how the development of palm oil and rubber production in Rantau Karya Village in 2011-2017, how the palm distribution process and rubber in Rantau Karya Village in 2011-2017 and How do palm and rubber consumption activities in Rantau Karya Village in 2011-2017. The purpose of this study was to determine the economic development ofthe people of Rantau Karya Village, Air Sugihan Subdistrict, Ogan Komering Ilir Regency, 2011-2017 which focused on Rantau Karya Village in 2011-2017. The methodology used in this study is a historical method with steps: heuristics, criticism of sources, interpretation, historiography and in-depth interviews with community leaders in Rantau Karya Village. While the approach used is an economic, sociological and geographic approach, based on the results of research, it is found that the economic life of the community includes three aspects, namely in the fields of production, distribution and consumption. While the economic development seen is the development of agriculture in the plantation sector, namely oil palm and rubber plantations. Palm and rubber are the main income of the local community, this is in line with the increasing level of welfare of the people of Rantau Karya Village.